Creep behavior of as-cast Ti-48Al-2Cr intermetallic alloy for aerospace and automotive applications - Hamzah, Esah; Kanniah, M.; Harun, M. (Francais & Taylor, 2007)
The creep properties of as-cast Ti-48Al-2Cr (at%) alloy which had been strengthen with addition of 2 at% Cr were investigated. Tensile creep experiments were performed in air at temperatures from 600-800Â°C and initial stresses ranging from 150 to 180 MPa. Stress exponent and activation energy were both measured. Data indicates that the alloy exhibits steady state creep behavior and the steady state creep rate is found to depend on the applied load and temperature. The measured power law stress exponent for steady state creep rate is found to be close to 3 and the apparent activation energy for creep is calculated to be 15.7 kJ/mol. The creep resistance of the present alloy was also compared with binary Ti-48Al (at%) to evaluate the effect of Cr addition on creep resistance of TiAl. It is concluded that addition of 2 at% of Cr does not have significant effect on the creep resistance of TiAl.